Recursos da psicanálise na psicoterapia de crianças vítimas de abuso sexual incestuoso - Simão, Paula Vanessa Pestana [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
Pesquisas sobre violência revelam que o Brasil possui altos índices de maus-tratos à infância e a juventude e apontam a violência sexual incestuosa, ou seja, as cometidas por parentes próximos (pais, tios, padrastos, dentre outros) como a mais freqüente. Uma das conseqüências desses altos índices de violência é o aumento do número de crianças vitimas de abusos sexuais incestuosos em busca de auxílio psicoterapêutico. Para atender essa demanda, é preciso que os profissionais estejam devidamente capacitados e, para isso, o desenvolvimento de estudos, pesquisas, supervisões e projetos de atuação, terapias que visem a refletir sobre o assunto são fundamentais. O objetivo deste estudo é contribuir para o entendimento do abuso incestuoso e suas conseqüências, tendo em vista demandas sociais atuais. A pesquisa teve como eixo teórico metodológico teorias psicanalíticas, desde Freud com a noção de trauma [ano] e estudos sobre a Sexualidade Infantil [ano] e, mais detidamente, Ferenczi que abordou a experiência de abuso,e outros. E com o objetivo de pensar sobre a possibilidade de lidar com esse trauma no contexto psicoterapêutico, foram utilizadas algumas teorias de Winnicott. Não temos resultados conclusivos, mas desenvolvemos base para uma primeira reflexão que leva em conta o desenvolvimento emocional da criança, principalmente quando esta passa por uma experiência real de sedução.

Research about violence discloses that Brazil possess high indices of bad-treatments to infancy and youth and point the incestuous sexual violence, or either, committed for next relatives (the parents, uncles, stepfathers, amongst others) as most frequent. One of the consequences of these high indices of violence is the increase of the number of children victims of incestuous sexual abuses in search of psychotherapy relief. To take care of this demand, it is necessary that the professionals be duly enabled e, for this, the development of studies, research, supervisions and projects of performance, therapies that they aim at to reflect about subject are basic. In the attempt to take care of the social and clinical demands generated by the sexual violence, this essay had for objective the development of a systemize study, that it could contribute with theoretical and practical aspects for the agreement of the incestuous abuse and its consequences. The researches had as method theoretical axle psychoanalyze theories. Some Freudians concepts had been chosen that understood the Incest; The formation of the trauma; e the Infantile Sexuality, as basic points inside of the psychoanalysis for the agreement of the Trauma of the Incest and its consequences for the victim. With the objective to reflect on the possibility to deal with this trauma in the psychotherapy context, some theories of Winnicott had been used. As result has a systematization of concepts already postulates for the psychoanalysis, organized of directed form, objectifying it understanding of the emotional development of the child when this it passes for a real experience of seduction, for then trying itself to help it to deal with the trauma.
Keywords: Crianças maltratadas sexualmente; Psicanalise; Psicoterapia; Incesto; Sedução; Psychoanalyze; Incestuous; Psychotherapy; Seduction; Abuses Sexual